Shifts in Moral Decision-Making Among College Students: A 15-Year Successive Independent Samples Study Utilizing a Real-Life Dilemma (Journal of Advanced Research in Social Sciences, 2025)
This study examines shifts in moral decision-making among college students over a 15-year period. Using a real-life ethical dilemma presented annually in an introductory child and adolescent development course at a U.S. college, the research explores how students respond to a scenario in which lawyers withhold information about an innocent man’s wrongful imprisonment to protect their careers. The objectives were to assess changes in students' ethical attitudes and behaviors, as well as the underlying reasons for those changes. Methodologically, both quantitative and qualitative data were collected to track trends in students' willingness to speak out against injustice. The results indicate a significant decline in students’ readiness to challenge ethical wrongdoing, mirroring broader societal shifts in moral priorities. This transformation reflects not only a change in moral decision-making but also in the rationale behind students’ choices. The findings suggest a need for further research to explore the societal influences and motivational factors driving these changes. The study’s implications call for targeted interventions aimed at fostering ethical behavior and promoting integrity within educational and professional environments.